2014
DOI: 10.3389/fnhum.2014.00189
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to emotional expression information in high- and low-spatial frequency in autism: evidence for a cortical dysfunction

Abstract: Despite an overall consensus that Autism Spectrum Disorder (ASD) entails atypical processing of human faces and emotional expressions, the role of neural structures involved in early facial processing remains unresolved. An influential model for the neurotypical brain suggests that face processing in the fusiform gyrus and the amygdala is based on both high-spatial frequency (HSF) information carried by a parvocellular pathway, and low-spatial frequency (LSF) information separately conveyed by a magnocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 110 publications
3
21
0
Order By: Relevance
“…Thereby, our results might be evidence that the perception of emotional facial expressions depends on a neural network that entails the perception of changeable features of the human face that are crucial for social communication (Deen & Saxe, 2019;Andrews & Ewbank, 2004). The decrease in the modulation of the temporal brain region observed in pASD ( Figure 5, bottom line, left row) might reveal that differences between ASD and neurotypical development in cortical processing of faces expressing emotion could be broader and more complex than a mere consequence of social difficulties, and should receive more attention in future research (Billeci et al, 2016;Gerdts and Bernier, 2011;Sucksmith et al, 2011, Spencer et al, 2011Corradi-Dell'Acqua et al, 2014;Jackson et al, 2013). Indeed, the activation of this brain area correlates negatively with the symptomatology of their children (in terms of ADOS-2 score).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereby, our results might be evidence that the perception of emotional facial expressions depends on a neural network that entails the perception of changeable features of the human face that are crucial for social communication (Deen & Saxe, 2019;Andrews & Ewbank, 2004). The decrease in the modulation of the temporal brain region observed in pASD ( Figure 5, bottom line, left row) might reveal that differences between ASD and neurotypical development in cortical processing of faces expressing emotion could be broader and more complex than a mere consequence of social difficulties, and should receive more attention in future research (Billeci et al, 2016;Gerdts and Bernier, 2011;Sucksmith et al, 2011, Spencer et al, 2011Corradi-Dell'Acqua et al, 2014;Jackson et al, 2013). Indeed, the activation of this brain area correlates negatively with the symptomatology of their children (in terms of ADOS-2 score).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that ASD affects face perception (Luyster et al, 2014;Chawarska, Ye, Shic, & Chen, 2016;Jones & Klin, 2013). These impairments seem to depend on the spatial frequency of the visual stimuli (McCleery et al, 2007;Jackson et al, 2013;Corradi-Dell'Acqua et al, 2014). The perception of different spatial frequencies of visual stimuli relies on two types of retinal neurons that process either fine or coarse resolution of the visual signal (Vuilleumier et al, 2003;Boutet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, spatial frequency filtering may not be an effective way of isolating subcortical input to the amygdala via the pulvinar (although it remains to be seen whether it still may be viable for isolating input from the superior colliculus, specifically). This is a critical contribution to the current literature on emotion processing, which has already made inferences about autism by using spatial frequency as a proxy for subcortical processing (Corradi-Dell'Acqua et al, 2014).…”
Section: The Amygdala Rapidly Receives a Broad Range Of Visual Informmentioning
confidence: 99%